Monetary policy, financial conditions, and financial stability - Tobias Adrian; Nellie Liang (Federal Reserve Bank of New York, 2014)
In the conduct of monetary policy, there exists a risk-return trade-off between financial conditions and financial stability, which complements monetary policy's traditional trade-off between inflation and real activity. The trade-off exists even if monetary policy does not target financial stability considerations independently of its inflation and real activity goals, because risks to future financial stability are increased by the buildup of financial vulnerabilities from persistent accommodative monetary policy when the economy is close to potential. We review monetary policy transmission channels and financial frictions that give rise to this trade-off between financial conditions and financial stability, within a monitoring program across asset markets, banking firms, shadow banking, and the nonfinancial sector. We focus on vulnerabilities that affect monetary policy's risk-return trade-off, including 1) pricing of risk, 2) leverage, 3) maturity and liquidity mismatch, and 4) interconnectedness and complexity. We also discuss the extent to which structural and time-varying macroprudential policies can counteract the buildup of vulnerabilities, thus mitigating monetary policy's risk-return trade-off.
Keywords: E52; G01; G28; 330; risk-taking channel of monetary policy; monetary policy transmission; monetary policy rules; financial stability; financial conditions; macroprudential policy